A large-scale RNAi screen identifies Deaf1 as a regulator of innate immune responses in Drosophila - Kuttenkeuler, David; Pelte, Nadège; Ragab, Anan; Gesellchen, Viola; Schneider, Lena; Blass, Claudia; Axelsson, Elin; Huber, Wolfgang; Boutros, Michael (Journal of innate immunity, 2010)
Innate immune signalling pathways are evolutionarily conserved between invertebrates and vertebrates. The analysis of NF-ĸB signalling in Drosophila has contributed important insights into how organisms respond to infection. Nevertheless, significant gaps remain in our understanding of how the activation of intracellular signalling elicits specific transcriptional programs. Here we report a genome-wide RNA interference survey for transcription factors that are required for Toll-dependent immune responses. In addition to the NF-ĸB homologs Dif, Dorsal and factors of the general transcription machinery, we identified Deformed Epidermal Autoregulatory Factor 1 (Deaf1) to be required for the expression of the Toll target gene Drosomycin in cultured cells and in Drosophila in vivo. We show that Deaf1 is required for the survival of flies after fungal, but not E. coli, infection. We determine that Deaf1 acts downstream of the NF-ĸB factors Dorsal and Dif. These results indicate that Deaf1 is an important contributor to innate immune responses in vivo.
Online veröffentlicht: Oktober 13, 2009
Gesehen am 09.03.2023